Indirect validation of daily increments in whitemouth croaker (Micropogonias Furnieri) larvae otoliths - Braverman, Mara Silvia (2015)
The indirect validation in increments (rings) counting by a precision analysis allowed to determine the daily deposition pattern in whitemouth croaker (Micropogonias furnieri) otoliths during the larval and early juvenile stages. To compare the number of rings in each individual both sagittae otoliths (n= 71) and the readings by two independents readers (n= 27) were used. A slight variation of the optic focus allowed to eliminate sub-daily increments and obtain the best reading plane of the daily growth pattern. Between the 28th and 35th increment, approximately, the growing otoliths showed a rather diffuse zone where accessory nuclei around the main nucleus appeared. From the 35th increment onwards another deposition pattern markedly different from that of the accessory nuclei was noticed. The slopes of the linear regressions fitted between the otoliths of the pair and between the ones observed on the same otolith by the independent readers did not show significant differences with respect to 1. The analysis replicated and the intervention of two skilled independent readers constituted a consistent method to identify the daily deposition pattern in otoliths of the species larvae and early juveniles.